The influence of strength on the gymnasts' success in performing vault - Paunovic, M.; Velikckovic, S.; Okicic, T.; Jovic, S.; Ðordevic, D. (Science of Gymnastics Journal, 2022)
The aim of the study was to determine the influence of absolute and relative strength of the muscles of the legs, upper arms and shoulder girdle on the success of performing vault with gymnasts aged 13 to 16 who have been training gymnastics from five to 12 years. The Japanese digital dynamometer IMADAZ2H-1100 with WinWedge 3.4 software was used to estimate the absolute strength of the leg, upper arm and shoulder girdle muscles. The values shown on the digital meter represented the absolute value of the maximum force, and when the absolute value of the force was divided by the weight of the participant, the value of the relative force was obtained. Regression analysis was used to determine the influence of absolute and relative strength of leg muscles, upper arm and shoulder girdle on the success of performing vault. The results showed that although there is an influence of the above muscles, it is not statistically significant. Specifically, for a successful performance on the vault, the muscles of the shoulder girdle have the greatest influence (without statistical significance). The reason for the results obtained in this way lies in the fact that the phase of flight and landing depends on the support phase and the repulsion from the vault. As there are few research studies on the subject of this paper, regardless of the obtained results, this research represents a good foundation and basis for some future research of absolute and relative strength in artistic gymnastics.